Religious Moderation in PAI Learning: Local Wisdom of Sunan Kudus - Ahmad Falah; Muhdhor Muhammad Sodiqin; Dany Miftah M. Nur; Muhammad Yusril Muna (Cendekia: Kependidikan dan Kemasyarakatan, 2026)
Religious moderation has become a strategic issue in contemporary Islamic education due to the increasing challenges of intolerance, religious exclusivism, and social fragmentation in multicultural societies. This study aims to analyze the implementation of Islamic Religious Education (PAI) learning grounded in the local wisdom of Sunan Kudus as a pedagogical strategy to strengthen religious moderation at SMK Raden Umar Said Kudus and SMAN 01 Bae Kudus. This research employed a qualitative approach with a multi-site case study design. Data were collected through participatory observation, in-depth interviews, and documentation studies. Data analysis was conducted through the stages of data condensation, data display, and conclusion drawing, combined with thematic analysis. The findings reveal that the internalization of religious moderation was implemented through the integration of Sunan Kudus local wisdom values into the PAI curriculum, the application of reflective-dialogical learning strategies, teacher role modeling, and the habituation of attitudes that respect cultural and religious diversity. This study confirms that contextual Islamic learning based on local wisdom constitutes an effective pedagogical model for strengthening religious moderation and preventing intolerance in secondary education.